The Students’ Writing Anxiety at The Fourth Semester Students in Academic Writing Class - Prajna Fawwaza Alya Paramarti; Tusino Tusino; Sri Widodo; Edi Sunjayanto Masykuri (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
The purpose of this study was to find out how much writing anxiety exists among students, what causes it, and how to deal with it in academic writing courses. This research uses qualitative. This study was done at Universitas Muhammadiyah Purworejo using fourth-semester students who took an academic writing course as subjects. The findings revealed that the students' writing anxiety was in the high range (67.23). "High frequency of assignment" is a major cause of student writing anxiety in academic writing. The percentage obtained (31%), which was the highest among the components, showed this. Students overcame their writing anxieties by seeking assistance from friends, interacting with instructors, and reviewing journal references. It is possible to deduce that the students who took the academic writing course expressed worry.